2012
DOI: 10.3182/20120328-3-it-3014.00076
|View full text |Cite
|
Sign up to set email alerts
|

On event-based PI control of first-order processes

Abstract: Abstract:In this paper the design of an event-based proportional-integral (PI) control scheme for stable first-order processes is considered. A novel triggering mechanism which decides the transmission instants based on an estimate of the PI control signal is proposed. This mechanism addresses some sideeffects that have been discovered in previous event-triggered PI proposals, which trigger on the process output. In the proposed scheme, the classic PI controller is further replaced with PIDPLUS, a promising ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…This behavior is caused by the sticking effect (Tiberi et al 2012;Vasyutynskyy and Kabitzsch 2006), where, in this case, the severe actuator saturation avoids further events after the second event time (indicated by the second star in the upper plot of the figure). As the state information used by the controller deviates from the operating point at that time instance, the controller state x c (t) increases monotonically for all future times.…”
Section: Behavior Of the Event-triggered Control Loopmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior is caused by the sticking effect (Tiberi et al 2012;Vasyutynskyy and Kabitzsch 2006), where, in this case, the severe actuator saturation avoids further events after the second event time (indicated by the second star in the upper plot of the figure). As the state information used by the controller deviates from the operating point at that time instance, the controller state x c (t) increases monotonically for all future times.…”
Section: Behavior Of the Event-triggered Control Loopmentioning
confidence: 99%
“…Two general problems of event-triggered PID control are the sticking effect and large stationary oscillations (see Årzén 1999;Vasyutynskyy and Kabitzsch 2006). To overcome these problems two adaptations of the event-triggered control loop have been proposed by Tiberi et al (2012). By using a modified event condition based on the control inputũ(t) and by adapting the integrator part of the event-triggered PI-control loop considered, it has been shown that for stable first-order systems oscillations can be avoided and setpoint tracking is guaranteed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Sánchez, Visioli, and Dormido (2011) tuning rules arise from time-based approaches. In Tiberi and Johansson (2012) authors mention a specific tuning procedure for the PIDplus controller according to the methodology proposed in Otanez, Moyne, and Tilbury (2002) but its influence on system performance or stability is not described. In and tuning rules are defined using trialand-error methods with the aim of improving a performance index (typically, the energy consumption of wireless sensors).…”
Section: Introductionmentioning
confidence: 98%
“…Few researchers address the setpoint tracking problem in the event-triggered control framework, see [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. An early approach of event-triggered PI control [7] has shown that the communication effort can be significantly reduced with little degradation of the control performance compared with the time-based counterpart.…”
Section: Introductionmentioning
confidence: 99%